Angiogenin—A Proposed Biomarker for Cardiovascular Disease—Is Not Associated With Long-Term Survival in Patients With Peripheral Artery Disease. (October 2021) - Höbaus, Clemens; Pesau, Gerfried; Zierfuss, Bernhard; Koppensteiner, Renate; Schernthaner, Gerit-Holger
We evaluated angiogenin as a prospective biomarker in peripheral artery disease (PAD) patients with and without claudication symptoms. A pilot study suggested an elevation of angiogenin in critical limb ischemia. However, in PAD patients, the predictive value of angiogenin has not yet been evaluated. For this purpose, 342 patients with PAD (age: 69 ± 10 years, 34.5% women) were followed-up for 7 years in a cross-sectional study. Angiogenin was measured by enzyme-linked immunosorbent assay. All-cause and cardiovascular mortality were analyzed by Cox regression. Angiogenin levels were higher in men ( P = .001) and were associated with patient waist-to-hip ratio ( P < .001), fasting triglycerides ( P = .011), and inversely with estimated glomerular filtration rate ( P = .009). However, angiogenin showed no association with age, characteristics of diabetes, markers of lipid metabolism, or C-reactive protein. Angiogenin did not correlate with markers of angiogenesis such as vascular endothelial growth factor, angiopoietin-2, or tie-2. Furthermore, angiogenin was not associated with PAD Fontaine stages or with patient ankle-brachial index in addition to all-cause mortality (hazard ratio [HR] = 1.09 [95% CI: 0.89-1.34]) or cardiovascular morality (HR = 1.05 [0.82-1.35]). These results suggest that angiogenin does not provide further information regarding outcome prediction in patients with PAD.